TO DETERMINE THE FREQUENCY OF HEPATIC VEIN VARIANTS IN NORMAL POPULATION: ROLE OF MDCT IN HEPATIC TRANSPLANTATION - Shakeel, Hamna; Ilyas, Muhammad; Butt, Rabia Waseem; Abbas, Hassan Burair; Abid, Anila; Niazi, Manal (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of hepatic vein variants in normal population.Study Disign: Cross sectional study.Place and Duration of Study: Department of Radiology, PAEC General Hospital, H-11/4 Islamabad, from Jul 2019 Dec 2020.Methodology: Sample size of 190 patients was calculated using WHO calculator. Patients were selected through non probability consecutive sampling. MDCT Scan was done in venous phase at 65-70s after injection of approximately 2ml/kg contrast material. The scan range was from diaphragm till Ischium using straight gantry plane. Image reconstruction and reformatting in coronal and sagittal images was obtained. Data was analyzed with SPSS program version 20.0. Chi-square test was applied. p-value ≤0.05 was considered significant.Results: Mean age was 35.56 ± 65.9 years with minimum and maximum of 25 & 45 years respectively. One hundred and thirty two (69.5%) patients were male and 58 (30.5%) patients were female respectively. One hundred and four (54.7%) of patients were of type I, 68 (35.8%) of patients were of Type II and 18 (9.5%) of patients were found with type III variant of hepatic vein. In age category (25-35 years.) Forty three, 26 and 7 were found with type I, II and III hepatic veins respectively. While in age category (36-45 years). Sixty one, 42 and 11 patients were found with type I, II and III variant of hepatic vein respectively. Further stratification with respect to age categories among the genders was done and tabulated.Conclusion: The prevailing patterns of three hepatic vein in this study are.........